Kebijakan Penerima Bantuan Iuran (PBI) Yang Tidak Tepat Sasaran : Telaah Berdasarkan Undang-Undang No 24 Tahun 2011 Tentang Sistem Jaminan Sosial Nasional - Baedarus, Siti Aulia; Arifin, Arifin; Atika, Vivi Della; Nabila, Bernika Salsa; Tuasamu, Zainab Nursidik (Journal of Industrial Relations Studies, 2026)
The National Health Insurance System (JKN) was established on January 1, 2014, by the Indonesian government as a major step towards the country's goal of providing equitable, fair, and affordable health services for all Indonesians. The JKN's objectives are based on Law No. 40 of 2004 concerning the National Social Security System and Presidential Regulation No. 12 of 2013 concerning Health Insurance. This study examines how the law is applied and propriety in the program for recipients of premium assistance who are not properly targeted, as well as legal protection for PBI issued by the government. This research method uses a normative juridical analysis method, namely by focusing on processing literature materials in case studies as a reflection of the implementation of law in the field of the national health insurance system